ANALISIS SELISIH KURS MATA UANG ASING TERHADAP LABA PT.BAI - Tommy Munaf,; Salihi, Salihi; Josephine Adrianata,; Andres Putranta Sitepu, (Juremi: Jurnal Riset Ekonomi, 2024)
The purpose of this research is to find out how to apply the settlement of exchange rate differences due to foreign currency transactions on profits at PT. BAI. This research aims to determine the exchange rate differences that occur in profits at company objects. The method used in this research is qualitative methods. The object of this research is PT. BAI. Data collection was carried out by means of interviews, literature study and documentation. The types of data used to conduct research are primary data and secondary data. Based on research conducted on the financial reports of PT. BAI for 3 years (2020-2022), it is known that the value of foreign exchange profits in the 2020 financial statements has an impact of IDR 126,565,476,210,-, in 2021 IDR 68,866,049,667,- and in 2022 the value of foreign exchange profits has an impact of IDR 50,233,503,450,-. Based on the results of the analysis, it is known that the value of foreign exchange profits actually adds to the value of the company's profits, but the company has applied the exchange differences that actually occurred in accordance with the applicable Financial Accounting Standards and are recorded separately in a separate account